Study of Methanol and Ethanol Absorption on Vacuum Temperature of Adsorption Cooling Machine Adsorption Cycle - Purba, Jhon Sufriadi; Saragi, Jandri Fan HT (Journal of Mechanical Engineering Science and Technology (JMEST), 2021)
Cooling machines are currently being used more and more in accordance with technological advances and increasing living standards. Common uses are for preserving food, air conditioning, cooling beverages, for making ice cubes, and others. The need for cooling systems in remote areas for various needs such as preservation or storage of food ingredients is felt to be increasing, while the existing conventional cooling systems cannot necessarily be used because not all remote areas have electricity networks, so a simple adsorption cooling system is an alternative for solving problems. cooling system needs in remote areas like this. The purpose of this study was to obtain the optimum vacuum temperature in an adsorption cooler using activated carbon as adsorbent and methanol and ethanol as adsorbate. In this study using the experimental method by analyzing the testing and data processing of methanol and ethanol. The results of this study indicate that the vacuum absorber temperature of the refrigerant (methanol) gets the maximum temperature: 123.53oC on a thermostat with a temperature of 200oC, it can absorb methanol as much as 6.35 ml/kg and produce a water temperature of 9.12oC. Meanwhile, the absorber vacuum temperature for refrigerant (Ethanol) has a maximum temperature of: 123,26oC, on a thermostat with a temperature of 200oC, it can absorb ethanol as much as 6.35 ml/kg and produce a water temperature of 11,79oC.